2016
DOI: 10.1002/oby.21410
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of roux‐en‐Y gastric bypass surgery on postprandial fructose metabolism

Abstract: Objective: Fructose is partly metabolized in small bowel enterocytes, where it can be converted into glucose or fatty acids. It was therefore hypothesized that Roux-en-Y gastric bypass (RYGB) may significantly alter fructose metabolism. Methods: We performed a randomized clinical study in eight patients 12-17 months after RYGB and eight control (Ctrl) subjects. Each participant was studied after ingestion of a protein and lipid meal (PL) and after ingestion of a protein1lipid1fructose1glucose meal labeled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 33 publications
3
25
1
Order By: Relevance
“…The study again demonstrated the capacity for DNL from fructose within human enterocytes [57]. In control subjects, the reported incremental area under the curve values (iAUC) for CM-[ 13 C]-palmitate were almost 2-fold greater than the VLDL-[ 13 C]-palmitate iAUC, suggesting enterocytes contributed more de novo palmitate to the overall circulating TRL-TG pool than hepatocytes.…”
Section: Fructose and Intestinal De Novo Lipogenesis (Dnl)mentioning
confidence: 87%
See 2 more Smart Citations
“…The study again demonstrated the capacity for DNL from fructose within human enterocytes [57]. In control subjects, the reported incremental area under the curve values (iAUC) for CM-[ 13 C]-palmitate were almost 2-fold greater than the VLDL-[ 13 C]-palmitate iAUC, suggesting enterocytes contributed more de novo palmitate to the overall circulating TRL-TG pool than hepatocytes.…”
Section: Fructose and Intestinal De Novo Lipogenesis (Dnl)mentioning
confidence: 87%
“…Emerging evidence from rodents and humans indicates that enterocytes may make a more meaningful contribution to fructose metabolism than previously thought [42,57]. This appears to include disposal of fructose carbons via DNL, providing de novo FA to the circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned studies of [56] and Surowska et al (2016) [57] provide some of the only available results to date regarding the effect of fructose on CM-TG levels, although they did not isolate specific CM and VLDL fractions as described above, but used the concentration of TG in the Sf > 400 fraction as a marker of CM-TG [56,57]. In the latter study, control subjects (no RYGB surgery) that consumed Fr + G in addition to ProLip tended to show an increased Sf > 400-TG response, with a larger delayed peak and higher iAUC over the 360 min time course, although these differences were not significant, perhaps owing to the low statistical power of the study and high inter-individual variation.…”
Section: Fructose Effects On Enterocyte Cm-tg Secretionmentioning
confidence: 99%
“…Interestingly, Intralipid plus glucose also increased the fractional clearance rate of TRP‐apo48. The group of Luc Tappy tracked the incorporation of 13 C into chylomicron and VLDL1 over 6 h in young normal weight and older overweight men who consumed meals consisting of 13 C‐labelled fructose, and unlabelled glucose, lipids and protein. The concentration of 13 C‐palmitate in chylomicron‐ and VLDL‐TG increased progressively after ingestion of 13 C‐fructose labelled meals in both groups of subjects, indicating that both intestinal and hepatic DNL contributed to the disposal of fructose carbons .…”
mentioning
confidence: 99%